THE QUALITY OF TREATMENT EVALUATION IN REGISTRIES FOR ACUTE CEREBRAL CIRCULATION DISORDERS. FOREIGN EXPERIENCE, RUSSIAN PERSPECTIVES - A. Yu. Suvorov; S. Yu. Martsevich; N. P. Kutishenko (Кардиоваскулярная терапия и профилактика, 2014)
In the review the most prominent foreign registries of stroke are explored, those concern the evaluation of the treatment, and several Russian registries. The importance of treatment evaluation is discussed, and better and worse sides of the evaluating systems are estimated as their possibility to be used it Russia.